2000
DOI: 10.1046/j.1525-1411.2000.24009.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Role of Prostate Specific Antigen Parameters in Clinical Practice

Abstract: Introduction: Serum prostate specific antigen at the cutoff levels of 4 ng/ml has low specificity for prostate cancer. We evaluated various PSA parameters (i.e., total PSA density [tPSAD], free PSA density [fPSAD], the ratio of free to total PSA [f/t ratio], and age-specific PSA) in terms of cancer diagnosis and reducing the number of negative results for prostatic biopsies. Materials and Methods: A series of 305 patients was studied. Serum tPSA and fPSA levels were measured. Prostate volume was measured with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…Prostatic adenocarcinoma mean age is 68.88±6.49 and more common between 61to 80 years of age in this study. In our study prostatic adenocarcinoma mean age figure are comparable with finding from other studies which report the mean age of 69 years by Thompson IM et al, [7] mean age of 65 years by Lyn et al, [8] and mean age of 68 years by H A Mwakyoma et al . [9] In the present study BPH cases are 79.83% which is nearby comparable with Kshitij et al, [10] Jeven et al, [12] Arunchitale et al [13] and Janardan et al studies.…”
Section: Discussionsupporting
confidence: 92%
“…Prostatic adenocarcinoma mean age is 68.88±6.49 and more common between 61to 80 years of age in this study. In our study prostatic adenocarcinoma mean age figure are comparable with finding from other studies which report the mean age of 69 years by Thompson IM et al, [7] mean age of 65 years by Lyn et al, [8] and mean age of 68 years by H A Mwakyoma et al . [9] In the present study BPH cases are 79.83% which is nearby comparable with Kshitij et al, [10] Jeven et al, [12] Arunchitale et al [13] and Janardan et al studies.…”
Section: Discussionsupporting
confidence: 92%
“…The various studies done by Mwakyoma and Mabandi showed 5.3%, 61.1% and 33.6% cases had Gleason score of 2-4, 5-7 and 8-10 respectively; Divrik et al observed 9.7%, 76.7% and 13.6% cases having Gleason score of 2-4, 5-7 and 8-10 respectively. [16][17][18][19][20][21][22][23][24][25] The results for the cases with Gleason scoring between 8-10 i.e poorly differentiated tumours are comparable to other studies. Thus, the present study shows more number of cases with gleason's score 2-4.…”
Section: Discussionsupporting
confidence: 68%
“…In view of high degree of association of HGPIN with prostatic carcinoma, it is suggested that these HGPIN patients need close follow-up, observations and investigations to rule out existence of carcinoma, especially in the peripheral zone. [15][16][21] 38 ( [15][16][17][18][19][20][21][22][23][24] In the present study, 38/150 cases (25.3%) showing prostatic adenocarcinoma, Gleason score of 2-4 (well differentiated), 5-6 (moderately differentiated), 7(moderately to poorly differentiated), 8-10 (poorly differentiated) were noted in 39.4%, 21.0%, 8.0% and 31.6% cases respectively. The various studies done by Mwakyoma and Mabandi showed 5.3%, 61.1% and 33.6% cases had Gleason score of 2-4, 5-7 and 8-10 respectively; Divrik et al observed 9.7%, 76.7% and 13.6% cases having Gleason score of 2-4, 5-7 and 8-10 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study mean age of adenocarcinoma was 75.62 years which is comparable to previously done studies. [6][7][8][9][10] In studies done by Kumaresan et al 4 and Shah RB et al, 11 the incidence of BPH with suspicious focus ranged from 26 -46%; in our study we found an incidence of 30%. Premalignant lesions like LGPIN and HGPIN in the present study had an incidence of 13.3% and 10% respectively which is similar to studies done by Rekhi et al 12 (11.2%) and Kumaresan et al8 (14.2%).…”
Section: Discussionsupporting
confidence: 44%